Evaluasi Rute dan Lokasi Halte Bus Rapid Transit (BRT) Koridor II di Palangka Raya - Fatta Ilyaza Fakhtian; Anton Budiharjo (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2021)
Palangka Raya City Government uses BRT as one of the modes of transportation,and has the goal of serving the needs of passenger requests. For BRT operations, supporting facilities are needed, such as bus stops. Because of the large costs in establishing a bus stop, the effectiveness of bus stop construction is needed. In this research, the set covering problem and max covering problem model are chosen using Lingo 18.0. The set covering problem model aims to provide passengers with a proper access to the nearest bus stop with a minimum number. While the max covering problem aims to determine the location of the bus stops to be built when there is a limit on the number of bus stops. This type of research is a survey field research, distributing questionnaires and direct observation. The route performance and operation of corridor II BRT are include the number of passengers transported, load factor, headway time, travel speed and transportation availability are not in accordance with the standards while the waiting time for passengers has met regulatory standards. The route of the corridor II BRT bus in Palangka Raya is in accordance with the location of the trip generation, but the schedule and operational routes each day are not. The optimal number of BRT Corridor II stops in Palangka Raya that correspond to the passenger generation is 12 stops which can serve all 32 requests, then in the sensitivity analysis 3 other alternatives are selected. The alternatives are 5,10 and 15.